Multi-step verification of the Copenhagen atomics molten salt experiment radioactive inventory at the Paul Scherrer Institute using OpenMC, Serpent, and EQL0D - Chierici, Lorenzo; Rossi, Alessio (Frontiers in Nuclear Engineering, 2025)
The molten salt experiment (MSE) is a 30-day 1 MW (thermal) molten salt criticality experiment designed by Copenhagen Atomics that will be conducted at the Paul Scherrer Institute (PSI) Swiss research center. A detailed analysis of the radioactive inventory available during the operation and after shutdown has been carried out for future estimates of potential source term release in case of undesired accidents using the Monte Carlo transport and depletion code OpenMC. To benchmark the radioactive inventory obtained through the OpenMC burn-up calculation (version 0.15.2), code-to-code comparison with the Serpent Monte Carlo and depletion code (v2.2.1), as well as with Serpent coupled to the EQL0D depletion module developed at PSI, were performed. All of the utilized codes support neutron transport on CAD-based geometries and allow continuous material reprocessing during depletion. This feature is essential for modeling the MSE concept, where gaseous fission products are continuously extracted from the circulating fuel salt. For the present verification study, three models of increasing geometric and physical detail were developed: (1) a nested hollow sphere model in constructive solid geometry (CSG), with the scope of aligning basic settings beyond geometry; (2) a geometrically simplified CAD model of the Copenhagen Atomics Onion Core, mainly utilized for testing the integration of CAD models within the above depletion codes; (3) the same simplified CAD model but with the implementation of reactor fluid flows from the inner active core to the outer inactive region, mainly to account for the effect of out-of-core decay. The results were compared to benchmark the original OpenMC model. Particular attention was given to the end-of-cycle (EOC) isotopic inventory, with detailed comparisons for key radionuclides and total radiotoxicity.